Ankle‐brachial index long‐term outcome after first‐ever ischaemic stroke. Issue Volume 20:Issue11(2013:Nov.) (7th June 2013) - Milionis, H.; Vemmou, A.; Ntaios, G.; Makaritsis, K.; Koroboki, E.; Papavasileiou, V.; Savvari, P.; Spengos, K.; Elisaf, M.; Vemmos, K.
<x xml:space="preserve">Abstract</x> Background and purpose Ankle‐brachial blood pressure index (ABI) is a clinical tool to identify the presence of peripheral artery disease. There is a scarcity of data associating ABI with long‐term outcome in patients with IS. The association between ABI and long‐term outcome in patients with first‐ever acute IS was assessed. Methods Ankle‐brachial blood pressure index was assessed in all consecutive patients with a first‐ever acute IS admitted at Alexandra University hospital (Athens, Greece) between January 2005 and December 2010. ABI was considered normal when > 0.90 and ≤ 1.30. The Kaplan–Meier product limit method was used to estimate the probability of 5‐year composite cardiovascular event‐free (defined as recurrent stroke, myocardial infarction or cardiovascular death) and overall survival. A multivariate analysis was performed to assess whether ABI is an independent predictor of 5‐year mortality and dependence. Results Amongst 653 patients, 129 (19.8%) with ABI ≤ 0.9 were identified. Five‐year cumulative composite cardiovascular event‐free and overall survival rates were better in normal ABI stroke patients (log‐rank test: 7.22, P = 0.007 and 23.40, P < 0.001, respectively). There was no difference in 5‐year risk of stroke recurrence between low and normal ABI groups (hazard ratio, HR = 1.23, 95%CI 0.68–2.23). In multivariate Cox regression analysis, independent predictors of 5‐year mortality included age (HR = 2.55 per 10 years, 95%CI 1.86–3.48, P < 0.001), the National Institutes of Health Stroke Scale (per point increase HR = 1.12, 95%CI 1.08–1.16, P < 0.001), and low ABI (HR = 2.22, 95%CI 1.22–4.03, P = 0.009). Age (HR = 1.21 per 10 years, 95%CI 1.01–1.45, P = 0.04) and low ABI (HR = 1.72, 95%CI 1.11–2.67, P = 0.01) were independent predictors of the composite cardiovascular end‐point. Conclusions Low ABI in patients with acute IS is associated with increased 5‐year cardiovascular event risk and mortality. However, ABI does not appear to predict long‐term stroke recurrence.